PROJECT BASED LEARNING DALAM PEMBELAJARAN PKN : PERSPEKTIF GURU DAN SISWA SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how teachers and students perceive the implementation of project based learning in Civic Education (PKn) in a fourth grade elementary classroom and identifies factors that influence its implementation. The study addresses the need to understand classroom experiences during project based instruction and how these experiences shape learning engagement. A qualitative case study design was employed, involving a fourth grade teacher and students as research participants. Data were collected through structured interviews, classroom observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings show that the implementation of project based learning is shaped by several interconnected factors, including the use of driving questions, the organization of project activities, group collaboration, and the relevance of learning materials to students’ real life contexts. Students demonstrated active participation during project activities, showed positive responses toward collaborative work, and engaged in simple discussions to complete assigned tasks. The study indicates that project based learning creates a structured yet flexible learning environment that supports student involvement and contextual understanding. It concludes that the effectiveness of project based learning depends on how teachers design and manage project activities in alignment with classroom conditions.